Experimental Study on Unconfined Compressive Strength of Organic Polymer Reinforced Sand - Jin Liu; Qiao Feng; Yong Wang; Da Zhang; Jihong Wei; Debi Prasanna Kanungo (International Journal of Polymer Science)
The natural sand is loose in structure with a small cohesive force. Organic polymer can be used to reinforce this sand. To assess the effectiveness of organic polymer as soil stabilizer (PSS), a series of unconfined compressive strength tests have been performed on reinforced sand. The focus of this study was to determine a curing method and a mix design to stabilize sand. The curing time, PSS concentration, and sand density were considered as variables in this study. The reinforcement mechanism was analyzed with images of scanning electron microscope (SEM). The results indicated that the strength of stabilized sand increased with the increase in the curing time, concentration, and sand density. The strength plateaus are at about curing time of 48 h. The UCS of samples with density of 1.4 g/cm3 at 10%, 20%, 30%, 40%, and 50% PSS concentration are 62.34 kPa, 120.83 kPa, 169.22 kPa, 201.94 kPa, and 245.28 kPa, respectively. The UCS of samples with PSS concentration of 30% at 1.4 g/cm3, 1.5 g/cm3, and 1.6 g/cm3 density are 169.22 kPa, 238.6 kPa 5, and 281.69 kPa, respectively. The chemical reaction between PSS and sand particle is at its microlevel, which improves the sand strength by bonding its particles together and filling the pore spaces. In comparison with the traditional reinforcement methods, PSS has the advantages of time saving, lower cost, and better environment protection. The research results can be useful for practical engineering applications, especially for reinforcement of foundation, embankment, and landfill.